Rights of unionism under Malaysian industrial relations law: theory and reality / Mohd Hafizullah Abdullah…[et al.] - Abdullah, Mohd Hafizullah; Md Aris, Nur Zafirah; Mohamad Asraff, Sorfina; Tuan Kamaruzaman, Tengku Eliana (2009)
The practice of right of unionism in Malaysia is different as compared with theory and reality. Trade union is important in order to protect and fights the rights of employees. The aim of this research is to identify the forms of interventions in practising rights of unionism among employees in Malaysia. In Chapter 1 discussed forms of interventions at the early stage of formation. Chapter 2 is emphasized on analysis of trade union in Malaysia. This includes historical development, definition of trade union from legal provisions, rights to form under various legislations and formation and conditions of formation. Chapter 3 discussed the restrictions in forming trade union in Malaysia. There are several restrictions which are definition, membership of union, recognition and power of Director General of Trade Union. It also focuses on the restrictions under Federal Constitution, Trade Unions Act 1959 and Industrial Relations Act 1967. Chapter 4 discussed the implications of various interventions that had been discussed in Chapter 3. The last chapter underlined the recommendations from various respondents and from the point of view of the researchers.